SELF EFFICACY SISWA DALAM PEMBELAJARAN IPA - ayu astiti, kadek; Merry Yunithasari, Ni Putu; Muh Yusuf, Yusniati H. (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
Self-efficacy is an individual's belief in their ability to organize and carry out the necessary actions to complete certain tasks to achieve desired goals. Self-efficacy is one of the factors that influences student learning success. This study aims to analyze students' self-efficacy in science learning, the role of self-efficacy, and strategies to improve student self-efficacy in elementary school learning. The method used is a literature review method by analyzing the results of previous studies from various sources in national and international journals. The results obtained in this study are that self-efficacy has a positive effect on motivation, persistence, problem-solving abilities, and self-regulation. This has an impact on student success in carrying out the learning process and improving student achievement. Students who have high self-efficacy tend to be more enthusiastic and do not give up easily when facing challenges given tasks, thus providing maximum results in problem solving and success in the learning process. Strategies that can be done to improve student self-efficacy include providing successful experiences, experiential learning, approaches that adapt to students' abilities and needs, providing positive feedback, and maintaining students' emotional condition.